Peningkatan Hasil Belajar Peserta Didik Mata Pelajaran Ekonomi dengan Penggunaan Metode Ceramah Bervariasi - Triana Susanti; Supardi Supardi (Neraca: Jurnal Pendidikan Ekonomi, 2019)
This study aims to: (1) describe the learning activities of students with the use of varied lecture methods with assignments and question and answer; (2) to find out the improvement in student learning outcomes in economic subjects with the use of lecture methods varies with the assignment of assignments and question and answer at Katingan Hilir Kasongan State Senior High School. The method in this study is qualitative and quantitative methods with the type of Classroom Action Research (CAR). Subjects in this study were students of class XI IPS with a total of 23 students. Data collection techniques in this study were using observation and tests. The data analysis technique in this study uses percentages. The results showed that: (1) with the use of lecture methods varied with assignments and question and answer students became more active, this was evidenced by the data obtained, namely in cycle I 2.5 and had entered the criteria enough and in the implementation of the second cycle of 2.9 and has achieved good criteria, (2) With the use of lecture methods vary with the assignment of tasks and question and answer, there is an increase in student learning outcomes. This can be seen from the percentage of student learning outcomes in the first cycle which is equal to 78, 26%, namely as many as 18 students who complete and in the implementation of the second cycle that is achieving class completeness where students who complete as many as 23 students or 100% complete. This means that the use of the lecture method varies with the assignment of assignments and question and answer can improve student learning outcomes on economic subjects.